Psikoedukasi “IKESMEN” Untuk Meningkatkan Literasi Kesehatan Mental Siswa pada Guru - Runi Rulanggi; Thomas Dicky Hastjarjo (Faculty of Psychology, Universitas Gadjah Mada, 2016)
This study was to determine the effects of “Ikesmen” (e-mental health)Psychoeducation program in improving mental health literacy in secondary school teachersin Yogyakarta. Thirty secondary school teachers in Yogyakarta participated in the study.Fifteen teachers in the experimental group received “Ikesmen” program and fifteen teachers inthe control group did not receive treatment. The untreated control group design with pretestand posttest samples were used. The validity of “Ikesmen” program was tested in accordanceto Rusell module development principles (V coefficient is 0.775-0.8461). LiteracyQuestionnaires, Mental Health Stigma Questionnaires, and Mental health Knowledge Testwere used to collect data. Mixed analysis of variance was conducted to analyse the data. Theresults showed that there were no differences in the scores of mental health literacy betweenthe experimental group and control group (F=0.188, p =0.01< 0.668). There was no significantimprovement in the experimental group treated with Ikesmen Psychoeducation in comparisonwith the control group (F=0.640, p= 0.01<0.431). Further research is required to obtaindescription on the impact of technology usage in improving mental health literacy.